2009
DOI: 10.3168/jds.2008-1320
|View full text |Cite
|
Sign up to set email alerts
|

The addition of cottonseed hulls to the starter and supplementation of live yeast or mannanoligosaccharide in the milk for young calves

Abstract: The objectives of this study were to investigate the effects of the addition of cottonseed hulls (CSH) to the starter and the supplementation of live yeast product (YST) or mannanoligosaccharide product (MOS) to milk, on growth, intake, rumen development, and health parameters in young calves. Holstein (n = 116) and Jersey (n = 46) bull (n = 74) and heifer (n = 88) calves were assigned randomly within sex at birth to treatments. All calves were fed 3.8 L of colostrum daily for the first 2 d. Holstein calves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 24 publications
6
33
1
2
Order By: Relevance
“…The absence of significant effects for the addition of mannan-oligosaccharides in the diet of calves during the pre-weaning period was also observed in other studies (Sandi & Mülbach, 2001;Hill et al, 2009). However, these authors observed values numerically higher for starter intake for the calves supplemented with mannanoligosaccharides, likewise in the present study.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The absence of significant effects for the addition of mannan-oligosaccharides in the diet of calves during the pre-weaning period was also observed in other studies (Sandi & Mülbach, 2001;Hill et al, 2009). However, these authors observed values numerically higher for starter intake for the calves supplemented with mannanoligosaccharides, likewise in the present study.…”
Section: Resultssupporting
confidence: 61%
“…Dildey et al (1997) observed good results in performance, fecal score and reduction in mortality rate of dairy calves fed mannanoligosaccharides. In contrast, Hill et al (2009), in a recent study, concluded that Holstein calves do not respond to their inclusion in the milk replacer in regard to body growth, starter concentrate intake, rumen development and health parameters.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Os mananoligossacarídeos (MOS) fazem parte da fração carboidrato da parede celular, e são obtidos por meio da centrifugação de fragmentos de Saccharomyces cerevisae (HILL et al, 2009), que são posteriormente lavados e desidratados pelo método spray dry (SPRING et al, 2000). São formados por carboidratos não fermentáveis para alguns grupos de bactérias e apresentam como componente principal a D-mannose.…”
Section: Mananoligossacarídeosunclassified
“…Estudos com a inclusão de MOS tem apresentado bons resultados quanto ao desempenho, consumo de concentrado inicial e melhoras no escore de diarréia (KILLEN et al, 1994;SANDI;MÜHLBACH, 2001) para bezerros leiteiros da raça Holandês. Entretanto, em estudo recente, Hill et al (2009) compararam o efeito da suplementação com mananoligossacarideos a probiótico (Saccharomyces cerevisiae), em bezerros da raça Holandês e Jersey, quanto ao crescimento, ingestão de alimentos, desenvolvimento do rúmen e parâmetros de saúde na fase de aleitamento. Este estudo indicou que a suplementação do leite com MOS ou levedura pode beneficiar bezerros da raça Jersey, em todos os parâmetros avaliados, o que não foi observado em bezerros da raça Holandês.…”
Section: Mananoligossacarídeosunclassified